Running Mac OS X on Windows - Lee, Wei-Ming (O'Reilly short cuts., 2006)
For a long time, a lot of Windows users have been clamoring for the opportunity to run the Mac OS X operating system on their Windows PCs. As Mac OS X was designed to run on a different CPU architecture (PowerPC), running Mac OS X directly on Intel's CPU would not work. It wasn't until recently that PC users saw a ray of hope, when Apple announced that it was moving to Intel's CPU architecture and would hence port Mac OS X to run natively on Intel's x86 CPU architecture. However, the joy was short-lived, as Mac OS X can still run properly only on Apple's customized hardware, not commodity PCs.